General aspects about the structure of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) - Sotomayor Lugo, Francisco; Corbacho Padilla, JosÃ© Miguel; Valiente Linares, Ana Margarita; BenÃtez Cordero, Yudelkis; Viera GonzÃ¡lez, Tatiana (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: In late 2019, a new coronavirus named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that causes respiratory-related illness was reported in Wuhan, China. This virus can attack human lung cells causing a disease called coronavirus disease 2019 (COVID-19), which can lead to pneumonia and acute respiratory distress syndrome. Objective: Describe the structural characteristics of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Methods: A review was written from 47 bibliographic references. Articles and information from national and international journals available in the PubMed, Scopus, Medline, and SciELO databases were used. The quality, reliability and validity of the selected articles were analyzed to carry out an adequate review. Analysissynthesis and logical deduction methods were applied. Development: An introduction to the general aspects of the structure of SARS-CoV-2 is provided by stating the characteristics of the structural and non-structural proteins encoded by the viral genome, which provides the basis for understanding viral entry mechanisms to the host cell, and may be useful to stimulate the search for novel insights and possible therapeutic targets to fight the infection. Conclusions: Knowledge of the structure of the SARS-CoV-2 virus and the characteristics of the structural and non-structural proteins provides the basis for understanding the viral mechanisms of infection and the strategies for developing effective therapeutics.